The Making of Law Non-Participatory and Its Impact on Democracy - Wardana, Dodi Jaya (Universitas Muhammadiyah Surabaya, 2023)
The formation of laws in Indonesia today, both formally and materially, is still prone to deviations (controversy) by not involving public participation and not being open. This will result in problems in the form of legislative corruption, buying and selling articles, law products with weak legitimacy to Judicial Review. Public participation in the process of forming laws is an important element, because laws that are formed in a participatory manner are in line with democratic rule of law and meet the legal needs of society. Democracy. The focus of the study and analysis carried out in this research is related to the formation of an omnibus law (Cipta Kerja) which is considered undemocratic so that it poses a danger (legal consequences) and various responses from the community ranging from community rejection, students to workers who hold demonstrations. (demo) in various regions, then the submission of a judicial review at the constitutional court, then the inclusion of bills that are not important into the national legislation program and the existence of corruption in legislation in the law-making stage. This research is a normative legal research that aims to find solutions to legal issues and problems that arise in IndonesiaÂ in it, so that the results to be achieved then provide a prescription on what should be on the issues raised. The approach used is the law approach and the concept approach. The results of this study show that the process of forming the Omnibus law (Cipta Kerja) is full of interests, in this case the Government, DPR to Entrepreneurs so that it is not transparent (closed) and the lack of public participation which results in violations of democratic values and the constitution.Keywords: Formation of Laws; Not Participatory; Democracy.